Assessment of physicochemical, functional, thermal, and phytochemical characteristics of refined rice bran wax. (1st December 2022) - Modupalli, Nikitha; Thangaraju, Suka; Naik, G. Mohan; Rawson, Ashish; Natarajan, Venkatachalapathy
Highlights: RBW is highly similar to CW probably due to their plant origin. The thermal and crystallization behaviour of RBW is on par with CW. RBW contains bioactive compounds with anti-microbial activity. Abstract: The drastic increase in the utilization and conversion of biomass has been an effect of sustainability and circular economy in the food processing sector. Rice bran wax (RBW), an intermediate by-product of rice bran oil refining industries, has been one of the underutilized waste materials. The FT-IR analysis showed that RBW contains many similar compounds to that of beeswax (BW) and carnauba wax (CW). The DSC thermographs showed melting and crystallization temperatures of RBW as 78.55 and 73.43 °C, respectively, lesser than CW and more than BW. The peak profiling of XRD diffractographs has shown full-width at half-maximum of CW and RBW as 0.61 and 0.45, respectively, indicating distortion in crystal formation. The sequential extracts of RBW in hexane, dichloromethane, and ethylacetate have shown antimicrobial activity against E. coli and S. typhi . The research provides a baseline for extraction and separation of specialty compounds from RBW for by-product utilization.